Understanding the reactogenicity of 4CMenB vaccine: Comparison of a novel and conventional method of assessing post-immunisation fever and correlation with pre-release in vitro pyrogen testing. Issue 49 (17th November 2020) - Valente Pinto, Marta; Davis, Kimberly; Andrews, Nick; Goldblatt, David; Borrow, Ray; Southern, Jo; Nordgren, Ida Karin; Vipond, Caroline; Plested, Emma; Miller, Elizabeth; Snape, Matthew D.
Highlights: Use of continuous methods for temperature monitoring captured higher number of fever episodes. 4CMenB batches MAT scores did not correlate with fever episodes. The vaccine batches released were not associated with increased adverse events. Abstract: Background: Better understanding of vaccine reactogenicity is crucial given its potential impact upon vaccine safety and acceptance. Here we report a comparison between conventional and novel (continuous) methods of monitoring temperature and evaluate any association between reactogenicity and the monocyte activation test (MAT) employed for testing four-component capsular group B meningococcal vaccine (4CMenB) batches prior to release for clinical use in Europe. Methods: Healthy 7–12-week-old infants were randomised in two groups: group PCV13 2 + 1 (received pneumococcal conjugate vaccine 13 valent (PCV13) at 2, 4 and 12 months) and group PCV13 1 + 1 (received reduced schedule at 3 and 12 months). In both, infants received the remaining immunisations as per UK national schedule (including 4CMenB at 2, 4 and 12 months of age). Fever was measured for the first 24 h after immunisations using an axillary thermometer and with a wireless continuous temperature monitoring device (iButton®). To measure the relative pyrogenicity of individual 4CMenB batches, MAT was performed according to Ph. Eu. chapter 2.6.30 method C using PBMCs with IL-6 readout. Results: Fever rates detected by the iButton® ranged from 28.7% to 76.5% and from 46.6% to 71.1% in group PCV13 2 + 1 and PCV13 1 + 1 respectively, across all study visits. The iButton® recorded a higher number of fever episodes when compared with axillary measurements in both groups (range of axillary temperature fevers; group PCV13 2 + 1: 6.7%-38%; group PCV13 1 + 1: 11.4%-37.1%). An agreement between the two methods was between 0.39 and 0.36 (p < 0.001) at 8 h' time-point post primary immunisations. No correlation was found between MAT scores and fever rates, or other reported adverse events. Conclusions: It is likely that conventional, intermittent, fever measurements underestimates fever rates following immunisation. 4CMenB MAT scores didn't predict reactogenicity, providing reassurance that vaccine batches with the highest acceptable pyrogen level are not associated with an increase in adverse events. Clinicaltrials.gov identifier: NCT02482636.